STRUKTUR PENDAPATAN MASYARAKAT YANG TINGGAL DI DAERAH PINGGIRAN KOTA TONDANO - Menhard R. Manangkot; Olly Esry Laoh; Agnes E. Loho (COCOS, 2013)
ABSTRACTMenhard Richard Manangkot, Revenue structure of society which Living in SuburbanAreas Tondano under guidance of Esry .O. Laoh as Chairman and Agnes. E. Loho asmemberThe purpose of this study is to examine the structure of the income of people living inrural areas of Tondano and see how much additional revenue earned from the people whowork outside the agricultural sector. The results showed that the percentage of the incomestructure of the people living in the suburbs Tondano namely agriculture (42.5%), services(30%), PNS / private sector employees (17.5%) and Trade / point (10%). The family incomesuburban areas Tondano 62.36% came from non-agricultural sector and agricultural sector37.64%. For that extra income from non-agricultural sector by 12, 36%.